Analisis Faktor Perubahan Akad Murabahah menjadi Akad Rahn (Studi Kasus di BMT Surya Raharja Palang Tuban) - Sulis Setio Ningrum; Ahmad Afan Zaini; Elly Rustiana (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Banking is a very unique type. Its uniqueness lies in so many rules to protect all types of transactions. From the bank's internal side, regulations are made in such a way as to avoid risks that will bring material and immaterial losses. Many people in Indonesia do not yet know how the concept of how Islamic bank products work, especially in current financing products. Therefore, the basic thing for these banks must first be able to understand about financing products, especially murabahah financing and also financing using rahn contracts so that people can get to know them, and know more about products that are in accordance with BMT. With the existence of murabahah financing products and also financing with rahn contracts, people can carry out transactions in accordance with the applicable terms and conditions so that the transaction process can run smoothly. In this study, the authors used a qualitative type of research with a descriptive analysis approach. The method used in this study is the interview method and documentation from the financial institution concerned, which aims to answer the problem formulation raised by the author, namely: 1. What is the procedure for implementing murabahah and rahn contracts? 2. What factors cause the change of murabahah contract to rahn contract? The results of this study are: 1. There are basically two procedures for carrying out financing using murabahah and rahn contracts at BMT Surya Raharja, namely procedures in the field and also procedures in the office. 2. BMT Surya Raharja is a sharia-based financial institution, where in these financial institutions financing using a rahn contract is deemed more appropriate to apply than financing using a murabahah contract because financing using a rahn contract is more in line with financing that has been carried out at BMT Surya Raharja